Opportunities and Threats of Bank BRI KCP Kukar Tenggarong in Increasing the number of Tabungan Faedah BRI Syariah IB - Syarifah Syarifah; Sri Wahyuni (AFEBI Islamic Finance and Economic Review, 2021)
This study aims to provide an alternative strategy in facing opportunities to threaten the benefits of Tabungan Faedah BRI Syariah IB productat the Bank BRI Syariah KCP Kukar Tenggarong.This research used study of literature and SWOT analysis. SWOT analysis is the identification of various factors systematically to formulate a company strategy. This analysis is based on the logic that can maximize strengths and opportunities), but at the same time can minimize weaknesses and threats. The results of this study indicate that the BRI Syariah KCP Kukar Tenggarong bank has strengths, weaknesses, opportunities and threats to its product benefits. This research also provides 4 alternative strategies that can be used by banks in facing opportunities and threats. The 4 alternative strategies are the SO strategy, the WO strategy, the ST strategy and the WT strategy